On Noncommutative Paragraded Rings - Vuković, Mirjana (Sarajevo Journal of Mathematics, 2022)
Successful study of Bourbaki – Krasner’s graded structures problems opened the way to paragraded structures for me. In this paper we study paragraded modules over noncommutative paragraded rings and as a main result prove the paragraded version of Schur’s Lemma.